Impact Evaluation Design for Community Midwife Technicians in Malawi - Chimbatata, Nathan B.W.; Chimbatata, Chikondi M. (European Scientific Journal, ESJ, 2016)
Maternal Mortality Ratio and neonatal mortality rate are alarmingly high in Malawi. The shortage and poor retention of midwives coupled with poor working conditions have been a major challenge affecting the provision of high-quality maternity care for women. Many women are giving birth without skilled attendants, increasing the risk of maternal and neonatal illness and death. The major driving factor in the shortage of health staff is the limited number of existing training slots and hence the minimum output from the training institutions into service delivery units. Midwifery is a key component of sexual, reproductive, maternal, and newborn healthcare. Responding to the crisis, the Malawi Government has made a commitment in strengthening human resources for health, including accelerating training and recruitment of health professionals to fill all the shortage gaps in the health sector. One mechanism implemented by Malawi Government to increase skilled attendance at birth in rural areas is the introduction of Community midwifery assistants (CMA) training. This program of training community midwives is being piloted and targets the general population of pregnant women and their new born babies in rural areas where the CMAs are deployed. However, there is a great need to have this initiative evaluated and gauge its impact in attaining the desired outcomes.